(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
This research work investigated the potentials of unmodified Palm Kernel Fibers and its modified forms for the adsorption of Indigo blue dye from aqueous solutions using batch adsorption procedures. Characterization of the fibers were done with the scanning electron microscopy (SEM) and FTIR. Adsorption result showed that maximum uptake of 38.3, 31.0, 33.5 and 14.5 mg/g were respectively obtained for Bleached (BPKF), Acetylated (APKF), Mercerized (MPKF) and Unmodified Palm Kernel Fibers (UPKF) adsorbents at an optimum time of 3 hours. The sorption kinetic obeyed pseudo second order with the bleached adsorbent (BPKF) having the best fit, and at a certain time limit, intra-particle diffusion controlled the process. Data collected from effect of initial concentration experiments were better fit to the Freundlich isotherm. The result from the thermodynamics of the process showed an endothermic process. Increasing adsorbent dosages led to corresponding increase in the quantity of the indigo dye adsorbed by the different adsorbents. This work revealed the potentials of modified palm kernel fibers over the unmodified fiber for effective removal of Indigo blue dye from wastewater.